Aging differentially alters the transcriptome and landscape of chromatin accessibility in the male and female mouse hippocampus - Achiro, Jennifer M.; Tao, Yang; Gao, Fuying; Lin, Chia-Ho; Watanabe, Marika; Neumann, Sylvia; Coppola, Giovanni; Black, Douglas L.; Martin, Kelsey C. (Frontiers in Molecular Neuroscience, 2024)
Aging-related memory impairment and pathological memory disorders such as Alzheimer's disease differ between males and females, and yet little is known about how aging-related changes in the transcriptome and chromatin environment differ between sexes in the hippocampus. To investigate this question, we compared the chromatin accessibility landscape and gene expression/alternative splicing pattern of young adult and aged mouse hippocampus in both males and females using ATAC-seq and RNA-seq. We detected significant agingdependent changes in the expression of genes involved in immune response and synaptic function, and aging-dependent changes in the alternative splicing of myelin sheath genes. We found significant sex-bias in the expression and alternative splicing of hundreds of genes, including aging-dependent female-biased expression of myelin sheath genes and agingdependent male-biased expression of genes involved in synaptic function. Aging was associated with increased chromatin accessibility in both male and female hippocampus, especially in repetitive elements, and with an increase in LINE-1 transcription. We detected significant sexbias in chromatin accessibility in both autosomes and the X chromosome, with male-biased accessibility enriched at promoters and CpG-rich regions. Sex differences in gene expression and chromatin accessibility were amplified with aging, findings that may shed light on sex differences in aging-related and pathological memory loss. Keywords Aging; sex bias; hippocampus; gene expression; alternative splicing; ATAC-seq; chromatin accessibility; LINE-1 Introduction Aging is associated with cognitive decline and memory impairment, including spatial and episodic memory deficits (Nyberg et al., 2012). Research has revealed sex differences in memory performance with aging, as well as sex differences in the incidence of Alzheimer's disease, a condition associated with memory loss and damage to the hippocampal brain region (